Safety evaluation of an extension of use of the food enzyme pectinesterase from the genetically modified Aspergillus oryzae strain AR‐962 - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme pectinesterase (pectin pectylhydrolase; EC 3.1.1.11) is produced with the genetically modified Aspergillus oryzae strain AR‐962 by AB Enzymes GmbH. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in five food manufacturing processes. Subsequently, the applicant requested to extend its use to two additional processes. In this assessment, EFSA updated the safety evaluation of this food enzyme for uses in a total of seven food manufacturing processes. As the food enzyme–total organic solids (TOS) is removed from the final foods in three food manufacturing processes, the dietary exposure to the food enzyme–TOS was estimated only for the remaining four processes. Dietary exposure was up to 0.575 mg TOS/kg body weight (bw) per day in European populations. When combined with the NOAEL reported in the previous opinion (1000 mg TOS/kg bw per day, the highest dose tested), the Panel derived a margin of exposure of at least 1739. Based on the data provided for the previous evaluation and the revised margin of exposure, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.